Implementation of Building Character : Case Study at Madrasah Tsanawiyah Negeri 6 Sragen - Suryono, Suryono; Abbas, Ngatmin; Hidayah, Yayuk (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to examine the implementation of character building at MTsN 6 Sragen, as well as the supporting and inhibiting factors in the process. The background of this research stems from the importance of character education in shaping students with integrity, honesty, discipline, and responsibility. In an era of globalization filled with moral challenges, character education becomes a vital aspect that must be implemented in schools. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving teachers, students, and school staff at MTsN 6 Sragen. The research findings indicate that the implementation of character building at MTsN 6 Sragen has been effective, although some challenges remain, such as limited teaching time and minimal parental involvement. Other findings show that students participating in this program tend to exhibit better discipline and responsibility. The main supporting factors include the commitment of teachers in running the program and a conducive school environment. However, social media influence and lack of family engagement present the primary challenges. The study implies that the success of character education in schools requires strong collaboration between schools, families, and communities.